HUBUNGAN KONDISI SOSIAL EKONOMI ORANG TUA DENGAN HASIL BELAJAR GEOGRAFI SISWA KELAS XI SMA N 1 2x11 KAYUTANAM TAHUN PELAJARAN 2019/2020. - Cendani Jutin; Ernawati Ernawati (JURUSAN GEOGRAFI FIS UNP, 2021)
This study aims to determine the relationship between the socio-economic conditions of parents and the learning outcomes of class XI students of SMA N 1 2x11 Kayutanam in the 2019/2020 academic year. This research uses quantitative research which is classified as a correlation, the sample in the study consisted of 72 students of class XI SMA N 1 2x11 Kayutanam, the sample selection was carried out by total sampling method, namely all students of class XI IPS. Data collection techniques using a questionnaire or questionnaire given to students. Based on the research results, it can be concluded that the data analysis method used is Product Moment Correlation with r count 0.160 and r table 0.235 with the criteria rcount <rtabel or 0.160 <0.235. This shows that there is no significant relationship between the socioeconomic conditions of parents and student learning outcomes. The product moment coefficient of 0.160% results in a determination coefficient of 2.56%. This means that the socioeconomic conditions of parents affect student learning outcomes only 2.56%, while 97.44% are influenced by other factors not discussed in this study.